Kemandirian Anak Kelompok B Taman Kanak‐Kanak di TK Aisyiyah X Surakarta - Viona Rahmawati Jubaidah; Sri Ernawati; Faqih Purnomosidi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to assess the level of independence among Group B children at Aisyiyah X Kindergarten, Surakarta. Independence is essential for preparing children for future challenges. Using a descriptive qualitative approach with a case study method, this research involved four children and one teacher as informants. Data was collected through interviews, observations, and documentation. The findings revealed that Group B children demonstrated significant independence in their daily activities. They could complete tasks such as putting on their shoes, washing their hands, gathering and eating lunch, and tidying up their belongings without teacher assistance. Additionally, the children showed the ability to make choices, manage their time, control their emotions, and solve problems independently. Key factors contributing to their independence included the parenting styles of their families and the supportive routines in the school environment. Teachers played a crucial role in fostering this independence by assigning tasks that encouraged responsibility. These activities helped the children build self-management skills and confidence. Overall, the study found that Group B children at Aisyiyah X Kindergarten were well-equipped to carry out everyday tasks on their own, demonstrating a strong foundation for their future development.